USING INFORMATION TECHNOLOGIES IN «BIOCHEMISTRY» TEACHING OF MEDICAL UNIVERSITY STUDENTS - E. A. Teplyashina; E. V. Ermolovich (Russian State Vocational Pedagogical University, 2016)
The aim of the article is the description of a teaching software and the use of educational technology used in the discipline «Biochemistry», and the analysis of its effectiveness.Methods. The methods used in the work: a survey of students, observation, use of services Web 2.0: 1) Google Docs - for the development of questionnaires and statistical accumulation of responses; 2) You tube - for the development and publication of educational videos; 3) mindmeister.com - to prepare the mental maps; 4) Designerhttp://learningapps.org - to develop the game tasks. Results and scientific novelty. The possibilities of information technologies are analysed; the services to help develop a teaching support the learning process on the subject «Biochemistry» are selected. The references to scientific portals on the topic of this course are systematized. Subjects that attract the greatest interest of students are revealed and designated: «Protein metabolism», «Carbohydrate metabolism», «The enzymes and their importance in laboratory diagnosis». According to the identified themes the elements of the educational and methodical maintenance of the discipline «Biochemistry» on the basis of relevant services Web 2.0 are developed and tested. The high interest of students in mastering the discipline represented by the elements is found out. The proposed guidelines for teaching the subject «Biochemistry» based on acombination of traditional forms of learning are combined with the active use ofthe capabilities of modern information technologies.Practical significance. Developed by the authors technique can be used in planning and conducting of group and team work of medical university students while studying the fundamental disciplines of the university, as well as in the process of enhancing the skills of general practitioners.